Why House Price Indexes Differ : Measurement and Analysis - Silver, Mick (IMF Working Papers; Working Paper ;, 2012)
A key element in the build-up to the global recession and subsequently was the movement in house price indexes (HPIs). These indexes are particularly prone to methodological and coverage differences which can undermine both within-country and cross-country economic analysis. The paper outlines key measurement issues and reports on empirical work using an international panel data set that (i) considers whether differences in HPI measurement matter and, if so, in what way, and (ii) revisits the measurement of global house price inflation and the modeling of the determinants of house price inflation using HPIs corrected for differences in measurement practice.